Perancangan Pembuatan Kapal Tenaga Surya Skala Miniatur - Suriyadi; Ungo Ibuhasa; Muhammad Abdillah; Rizki; La Ode Ahmad Barata; Samhuddin (Program Pendidikan Vokasi Teknik Mesin, 2022)
A solar-powered ship is a means of marine transportation that is designed in such a way that its use is different from ships in general. This ship relies on solar energy as the main fuel so that this ship uses solar panels to capture sunlight and is stored in batteries/batteries as energy to drive a DC motor so that the electric ship can move stably. The goal is to be able to complete the final task. The method used in this final project uses the method of collecting data by searching for books, journals and modules related to the design title as a reference for the tool that the researcher designed. The result of this design is that the solar powered electric boat with 250 watts of power takes 59 seconds at a distance of 10 meters. 23 cm using a 50 Watt solar panel, 12 Volt Battery/Battery and 12 Volt DC Dynamo/Motor. As a boat engine and also an electric boat, this is very good as an alternative means of transportation that is environmentally friendly with no operational costs and small maintenance costs.